A Comprehensive Sampling Study on SARS-CoV-2 Contamination of Air and Surfaces in a Large Meat Processing Plant Experiencing COVID-19 Clusters in June 2020. Issue 4 (11th April 2023) - de Rooij, Myrna M.T.; Sikkema, Reina S.; Bouwknegt, Martijn; de Geus, Yvette; Stanoeva, Kamelia R.; Nieuwenweg, Sigrid; van Dam, Adriana S.G.; Raben, Ceder; Dohmen, Wietske; Heederik, Dick; Reusken, Chantal; Meijer, Adam; et al.
Abstract : Comprehensive environmental sampling showed limited SARS-CoV-2 contamination of air and surfaces in a meat processing plant, despite a large proportion of workers testing SARS-CoV-2 positive. A strict COVID-19 policy was in place, suggesting that SARS-CoV-2 transmission may be controlled in meat processing plants by enforcing appropriate preventive and mitigation measures. Abstract : Objective: We aimed to assess SARS-CoV-2 contamination of air and surfaces to gain insight into potential occupational exposure in a large meat processing plant experiencing COVID-19 clusters. Methods: Oro-nasopharyngeal SARS-CoV-2 screening was performed in 76 workers. Environmental samples ( n = 275) including air, ventilation systems, sewage, and swabs of high-touch surfaces and workers' hands were tested for SARS-CoV-2 RNA by real-time quantitative polymerase chain reaction. Results: Twenty-seven (35.5%) of the (predominantly asymptomatic) workers tested positive with modest to low viral loads (cycle threshold ≥ 29.7). Six of 203 surface swabs, 1 of 12 personal air samples, and one of four sewage samples tested positive; other samples tested negative. Conclusions: Although one third of workers tested positive, environmental contamination was limited. Widespread SARS-CoV-2 transmission via air and surfaces was considered unlikely within this plant at the time of investigation while strict COVID-19 control measures were already implemented.